2019
DOI: 10.1017/s0267190519000126
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Up Intervention Studies to Investigate Real-Life Foreign Language Learning in School

Abstract: Intervention studies typically target a focused aspect of language learning that is studied over a relatively short time frame for a relatively small number of participants in a controlled setting. While for many research questions, this is effective, it can also limit the ecological validity and relevance of the results for real-life language learning. In educational science, large-scale randomized controlled field trials (RCTs) are seen as the gold standard method for addressing this challenge—yet they requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 52 publications
0
17
0
1
Order By: Relevance
“…From a pedagogical perspective, using a web-based intelligent CALL system such as the one used here can certainly serve as a complement to what is done in the classroom (see Meurers et al, 2019, for an instance of an ICALL system already being used in a school setting). One of the problems with learners in the classroom is the fact that there is insufficient L2 input, since time in class is limited (European Commission Eurydice Report, 2017; Suzuki et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…From a pedagogical perspective, using a web-based intelligent CALL system such as the one used here can certainly serve as a complement to what is done in the classroom (see Meurers et al, 2019, for an instance of an ICALL system already being used in a school setting). One of the problems with learners in the classroom is the fact that there is insufficient L2 input, since time in class is limited (European Commission Eurydice Report, 2017; Suzuki et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Zahonero and Degano (2016) noted the headway in metalinguistic awareness of learners via wiki-assisted language learning and translation as a collaborative computer-assisted specialised program. Finally, Meurers et al (2019) developed a webbased FeedBook to replace printed books providing immediate scaffolded feedback to exercises and randomized controlled field trials; then they concluded with its effectiveness on English language learners.…”
Section: Cognitive Skills and E-learning Platformsmentioning
confidence: 99%
“…As such, immediate feedback will yield reaching the learning outcomes, and it will also serve as a vehicle to achieve effective e-learning thoroughly employing 'electronic interactions' (Lee, 2002). This would entail unlimited access to the instructional contents in turn (Meurers, Kuthy, Nuxoll, Rudzewitz, & Ziai, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…classrooms, and collection data of more varied formats, i.e. not only featuring essays (Meurers et al, 2019;Norris and Ortega, 2009). The SweLL corpus we present in this article can help answer (at least) a number of the above-mentioned questions for L2 Swedish.…”
Section: Preparatory Stepsmentioning
confidence: 99%